Communicative Culture Formation of Future Social Workers in the Educational Process of Pedagogical University - Omelchenko, S.; Chernukha, N.; Spivak, Y.; Spivak, L.; Uteubaeva, E. (International Journal of Higher Education, 2020)
Article considers the essence of the process of communicative culture formation of future social workers in the educational process of the pedagogical university. The communicative culture is singled out and considered through an interdisciplinary approach in the professional education of social workers. The peculiarities of the communicative culture formation of future social workers in the educational process in the pedagogical university are highlighted. Emphasis is placed on the need to use various tools in the phenomenon under study, such as: verbal, non-verbal, information and communication. The students' attitude to the process of communicative culture formation of future social workers in the educational process of the pedagogical university are investigated. The results of the experimental study are described.
Keywords: professional education; social worker; verbal communication; nonverbal communication; information; communication